Polarizing plate composite and image display device
By using a polarizing plate composite composed of a linear polarizing plate, a 1/2 wavelength layer and an active energy ray curing adhesive in the image display device, the problem of uneven interference in the prior art is solved, and a better visibility effect is achieved.
Patent Information
- Application Number
- CN202510084875.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-28
- Filing Date
- 2019-09-19
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the polarizing plate composite has a problem of uneven interference in the image display device, which affects visibility.
The polarizing plate composite consisting of a linear polarizing plate, a 1/2 wavelength layer, an active energy ray curing adhesive, and a 1/4 wavelength layer are used to regulate the refractive index and angle relationship of each layer to suppress uneven interference.
The interference inequality is effectively suppressed and the visibility of the image display device is improved.
Smart Images

Figure CN119882120A_ABST
Abstract
Description
[0001] This application is a divisional application. The application number of the parent application is 201980063726.0 (PCT / JP2019 / 036742), the application date is September 19, 2019, and the invention name is: Polarizing plate complex and image display device Technical Field
[0002] The present invention relates to a polarizing plate composite and an image display device having the polarizing plate composite. Background Art
[0003] Conventionally, in image display devices, a method has been adopted in which an optical layered body having an antireflection property is disposed on the visible side of an image display panel to suppress a decrease in visibility due to reflection of external light.
[0004] As an optical laminate with anti-reflection performance, a circular polarizing plate composed of a linear polarizing plate and a phase difference layer is known. In the circular polarizing plate, the external light toward the image display panel is converted into linear polarized light by the linear polarizing plate, and converted into circular polarized light by the subsequent phase difference layer. Although the external light converted into circularly polarized light is reflected on the surface of the image display panel, the rotation direction of the polarization plane is reversed during the reflection, and after being converted into linear polarized light by the phase difference layer, it is blocked by the subsequent linear polarizing plate. As a result, the emission to the outside is significantly suppressed.
[0005] Japanese Patent Application Laid-Open No. 2018-17996 (Patent Document 1) states that in a polarizing plate with a phase difference layer having a plurality of phase difference layers, by adjusting the difference in average refractive index of the plurality of phase difference layers, unevenness in reflected light can be suppressed and visibility can be improved.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-17996 Summary of the invention
[0009] Problems to be solved by the invention
[0010] An object of the present invention is to provide a novel composite polarizing plate in which the occurrence of interference unevenness is suppressed, and an image display device including the composite polarizing plate.
[0011] Means used to solve problems
[0012] The present invention provides the polarizing plate composite and image display device shown below.
[0013] [1] A polarizing plate composite comprising, in this order, a linear polarizing plate, a half-wavelength layer, a first adhesive layer formed by curing an active energy ray-curable adhesive, and a quarter-wavelength layer,
[0014] The angle between the fast axis of the 1 / 2 wavelength layer and the transmission axis of the linear polarizing plate is 10° or more and 20° or less,
[0015] An absolute value of a difference between a refractive index of the first adhesive layer at a wavelength of 589 nm and a refractive index of the half wavelength layer in a fast axis direction at a wavelength of 589 nm is less than 0.05.
[0016] [2] The polarizing plate composite according to [1], wherein the refractive index of the first adhesive layer at a wavelength of 589 nm is less than 1.55.
[0017] [3] A polarizing plate complex according to [1] or [2], wherein the in-plane average refractive index of the 1 / 4 wavelength layer at a wavelength of 589 nm is less than 1.58, and the in-plane average refractive index is the average of the refractive index in the fast axis direction and the refractive index in the slow axis direction.
[0018] [4] A polarizing plate composite according to any one of [1] to [3], wherein the absolute value of the difference between the refractive index of the first adhesive layer at a wavelength of 589 nm and the in-plane average refractive index of the quarter-wave layer at a wavelength of 589 nm is less than 0.05, and the in-plane average refractive index is the average value of the refractive index in the fast axis direction and the refractive index in the slow axis direction.
[0019] [5] The polarizing plate composite according to any one of [1] to [4], which is a circularly polarizing plate.
[0020] [6] The polarizing plate complex according to any one of [1] to [5], wherein the half wavelength layer includes a phase difference display layer as a liquid crystal layer.
[0021] [7] The polarizing plate complex according to any one of [1] to [6], wherein the quarter wavelength layer includes a phase difference display layer as a liquid crystal layer.
[0022] [8] The polarizing plate composite according to any one of [1] to [7], wherein the thickness of the first adhesive layer is 5 μm or less.
[0023] [9] An image display device comprising an image display panel and the polarizing plate complex according to any one of [1] to [8] disposed on a viewing side of the image display panel.
[0024]
[10] The image display device according to [9], wherein the polarizing plate complex is arranged in a direction in which the linear polarizing plate is located on the viewing side.
[0025]
[11] The image display device according to [9] or
[10] , which is an organic electroluminescent display device.
[0026] Effects of the Invention
[0027] According to the polarizing plate composite of the present invention, interference unevenness can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view schematically showing an example of the polarizing plate composite of the present invention.
[0029] Figure 2 This is a schematic cross-sectional view schematically showing an example of a phase difference layer including a liquid crystal layer as a phase difference showing layer.
[0030] Figure 3 (A) to (D) are schematic cross-sectional views schematically showing an example of each production step of the method for producing the polarizing plate composite of the present invention.
[0031] Figure 4 (A) and (B) are schematic cross-sectional views schematically showing another example of each production step of the method for producing the polarizing plate composite of the present invention. DETAILED DESCRIPTION
[0032] Hereinafter, the polarizing plate composite and the image display device of the present invention will be described with reference to the drawings.
[0033] [Compound phase difference plate]
[0034] Figure 1 Schematic cross-sectional view schematically showing an example of the polarizing plate composite of the present invention. Figure 1 As shown, the polarizing plate complex 10 is stacked with a linear polarizing plate 13, a second adhesive layer 22, a 1 / 2 wavelength layer 11, a first adhesive layer 21, and a 1 / 4 wavelength layer 12 in this order. In the polarizing plate complex 10, the angle formed by the fast axis of the 1 / 2 wavelength layer 11 and the transmission axis of the linear polarizing plate 13 is 10° or more and 20° or less, preferably 12° or more and 18° or less, and more preferably about 15°. In the polarizing plate complex 10, the angle formed by the fast axis of the 1 / 4 wavelength layer 12 and the transmission axis of the linear polarizing plate 13 is preferably 70° or more and 80° or less, more preferably 72° or more and 78° or less, and further preferably about 75°. In the polarizing plate complex 10, the angle formed by the slow axis of the 1 / 2 wavelength layer 11 and the slow axis of the 1 / 4 wavelength layer 12 is preferably 55° or more and 65° or less, more preferably 57° or more and 63° or less, and further preferably about 60°. By laminating the layers so as to form such an angle, the polarizing plate composite 10 can be suitably used as a circularly polarizing plate.
[0035] Even if the relationship is other than the above-mentioned angles, a polarizing plate composite that can be suitably used as a circular polarizing plate can be formed. However, by satisfying the above-mentioned relationship, interference unevenness can be effectively suppressed even when the refractive index of the first adhesive layer at a wavelength of 589 nm is less than 1.55.
[0036] The thickness of the polarizing plate composite 10 is preferably 30 μm to 50 μm, more preferably 30 μm to 200 μm, and even more preferably 30 μm to 150 μm from the viewpoint of reducing the thickness.
[0037] The refractive index of the first adhesive layer 21 at a wavelength of 589 nm is referred to as “refractive index n21”. The first adhesive layer 21 has no phase difference, and the refractive index in any direction can be regarded as the same value. Therefore, “refractive index n21” can be a refractive index in any direction.
[0038] For the 1 / 2 wavelength layer 11, the refractive index in the slow axis direction at a wavelength of 589 nm is defined as “refractive index n11 x ", set the refractive index in the fast axis direction to "refractive index n11 y ", set the refractive index in the thickness direction to "refractive index n11 z ", change n11 x With n11 y The average value is set as the "in-plane average refractive index n11 x,y ", change n11 x With n11 y With n11 z The average value is set as the "three-dimensional average refractive index n11 x,y,z ". The average refractive index in the plane is n11 x,y and the three-dimensional average refractive index n11 x,y,z Each is assumed to be a value calculated using the following formula (1) and formula (2).
[0039] n11 x,y =(n11 x +n11 y ) / twenty one)
[0040] n11 x,y,z =(n11 x +n11 y +n11 z ) / 3 (2)
[0041] For the 1 / 4 wavelength layer 12, the refractive index in the slow axis direction at a wavelength of 589 nm is defined as “refractive index n12 x ", set the refractive index in the fast axis direction to "refractive index n12 y", set the refractive index in the thickness direction to "refractive index n12 z ", change n12 x With n12 y The average value is set as the "in-plane average refractive index n12 x,y ", change n12 x With n12 y With n12 z The average value is set as the "three-dimensional average refractive index n12 x,y,z ". The average refractive index in the plane is n12 x,y and the three-dimensional average refractive index n12 x,y,z Each is assumed to be a value calculated using the following formula (3) and formula (4).
[0042] n12 x,y =(n12 x +n12 y ) / twenty three)
[0043] n12 x,y,z =(n12 x +n12 y +n12 z ) / 3 (4)
[0044] <First Adhesive Layer>
[0045] The first adhesive layer 21 is formed by curing an active energy ray-curable adhesive. The thickness of the first adhesive layer 21 is preferably 0.1 μm to 50 μm, and more preferably 0.1 μm to 5 μm.
[0046] The refractive index n21 of the first adhesive layer 21 at a wavelength of 589 nm and the refractive index n11 of the half-wave layer 11 in the fast axis direction at a wavelength of 589 nm are y The absolute value X1 of the difference calculated by the formula (5) is less than 0.05, preferably less than 0.04.
[0047] X1=|n11 y -n21|(5)
[0048] Interference unevenness can be suppressed by making the first adhesive layer 21 and the 1 / 2 wavelength layer 11 satisfy the above relationship in terms of refractive index. In order to make the first adhesive layer 21 and the 1 / 2 wavelength layer 11 satisfy the above relationship in terms of refractive index, it can be achieved by, for example, adjusting the composition of the active energy ray-curable adhesive used in forming the first adhesive layer 21 or adjusting the liquid crystal material used in forming the 1 / 2 wavelength layer 11.
[0049] The refractive index n21 of the first adhesive layer 21 at a wavelength of 589 nm and the in-plane average refractive index n12 of the quarter-wave layer 12 at a wavelength of 589 nm arex,y The absolute value X2 of the difference between , calculated using the formula (6) is preferably less than 0.05, and more preferably less than 0.04.
[0050] X2=|n12 x,y -n21|(6)
[0051] Interference unevenness can be suppressed by making the first adhesive layer 21 and the quarter wavelength layer 12 satisfy the above relationship in terms of refractive index. In order to make the first adhesive layer 21 and the quarter wavelength layer 12 satisfy the above relationship in terms of refractive index, for example, it can be achieved by adjusting the composition of the active energy ray-curable adhesive used in forming the first adhesive layer 21 or adjusting the liquid crystal material used in forming the quarter wavelength layer 11.
[0052] The refractive index n21 of the first adhesive layer 21 at a wavelength of 589 nm is, for example, less than 1.55.
[0053] In the present invention, even when the refractive index n21 of the first adhesive layer 21 is less than 1.55, interference unevenness can be suppressed.
[0054] An active energy ray-curable adhesive is an adhesive that cures after being irradiated with active energy rays. Examples include cationically polymerizable active energy ray-curable adhesives containing epoxy compounds and cationic polymerization initiators; free radical polymerizable active energy ray-curable adhesives containing acrylic curing components and free radical polymerization initiators; active energy ray-curable adhesives containing both cationically polymerizable curing components such as epoxy compounds and free radical polymerizable curing components such as acrylic compounds, and containing cationic polymerization initiators and free radical polymerization initiators; and electron beam-curable adhesives that are cured by irradiating electron beams to active energy ray-curable adhesives that do not contain an initiator. Since free radical polymerization has a tendency to shrink greatly upon curing, cationically polymerizable active energy ray-curable adhesives containing epoxy compounds and cationic polymerization initiators are preferred.
[0055] The active energy ray-curable adhesive selected from the following epoxy compound and combined with a cationic polymerization initiator suitable therefor can omit the drying equipment usually required in the process of bonding the 1 / 2 wavelength layer to the 1 / 4 wavelength layer. The epoxy compound is an epoxy compound capable of cation polymerization and is liquid at room temperature. Even in the absence of a solvent, it has appropriate fluidity and imparts appropriate cured bonding strength. In addition, the curing speed can be accelerated by irradiating an appropriate amount of active energy rays, thereby increasing the production speed.
[0056] The epoxy compound used in such an adhesive may be, for example, a glycidyl ether of an aromatic compound or a chain compound having a hydroxyl group, a glycidyl amide of a compound having an amino group, an epoxide of a chain compound having a CC double bond, an alicyclic epoxy compound having a glycidyloxy group or an ethylene oxide group bonded directly or via an alkylene group to a saturated carbon ring, or an epoxy group bonded directly to a saturated carbon ring, etc. These epoxy compounds may be used alone or in combination. Among them, alicyclic epoxy compounds are preferably used because of their excellent cationic polymerizability.
[0057] Glycidyl ethers of aromatic compounds or chain compounds having hydroxyl groups can be produced, for example, by a method of adding and condensing epichlorohydrin to the hydroxyl groups of these aromatic compounds or chain compounds under alkaline conditions. Such glycidyl ethers of aromatic compounds or chain compounds having hydroxyl groups include diglycidyl ethers of bisphenols, polyaromatic ring epoxy resins, and diglycidyl ethers of alkylene glycols or polyalkylene glycols.
[0058] Examples of the diglycidyl ethers of bisphenols include glycidyl ethers of bisphenol A and oligomers thereof, glycidyl ethers of bisphenol F and oligomers thereof, and glycidyl ethers of 3,3′,5,5′-tetramethyl-4,4′-biphenol and oligomers thereof.
[0059] Examples of the polyaromatic ring type epoxy resin include glycidyl etherified products of phenol novolac resins, glycidyl etherified products of cresol novolac resins, glycidyl etherified products of phenol aralkyl resins, glycidyl etherified products of naphthol aralkyl resins, glycidyl etherified products of phenol dicyclopentadiene resins, etc. In addition, glycidyl etherified products of triphenols and oligomers thereof also belong to the polyaromatic ring type epoxy resins.
[0060] Examples of the diglycidyl ether of an alkylene glycol or polyalkylene glycol include glycidyl etherified products of ethylene glycol, glycidyl etherified products of diethylene glycol, glycidyl etherified products of 1,4-butanediol, and glycidyl etherified products of 1,6-hexanediol.
[0061] The glycidylamide of a compound having an amino group can be produced, for example, by a method of adding and condensing epichlorohydrin to the amino group of the compound under alkaline conditions. The compound having an amino group may also have a hydroxyl group. The glycidylamide of such a compound having an amino group includes glycidylamide of 1,3-phenylenediamine and its oligomers, glycidylamide of 1,4-phenylenediamine and its oligomers, glycidylamide and glycidylether of 3-aminophenol and its oligomers, glycidylamide and glycidylether of 4-aminophenol and its oligomers, etc.
[0062] Epoxides of chain compounds having C-C double bonds can be produced by epoxidizing the C-C double bonds of the chain compounds using peroxides under alkaline conditions. Chain compounds having C-C double bonds include butadiene, polybutadiene, isoprene, pentadiene, hexadiene, etc. In addition, terpenes having double bonds can also be used as epoxidation raw materials, and non-cyclic monoterpenes include linalool, etc. The peroxide used in epoxidation can be, for example, hydrogen peroxide, peracetic acid, tert-butyl hydroperoxide, etc.
[0063] The alicyclic epoxy compound in which a glycidyloxy group or an ethylene oxide group is bonded to a saturated carbon ring directly or via an alkylene group may be a glycidyl etherified product of a hydrogenated polyhydroxy compound obtained by hydrogenating the aromatic ring of an aromatic compound having a hydroxy group typified by bisphenols mentioned above, a glycidyl etherified product of a cycloalkane compound having a hydroxy group, an epoxide of a cycloalkane compound having a vinyl group, or the like.
[0064] The epoxy compounds described above are easily commercially available, and examples thereof include the “jER” series sold by Mitsubishi Chemical Corporation, “EPICLON” sold by DIC Corporation, “Epototo (registered trademark)” sold by Tohto Kasei Co., Ltd., “ADEKA RESIN (registered trademark)” sold by ADEKA Corporation, “DENACOL (registered trademark)” sold by Nagase ChemteX Co., Ltd., “DOW Epoxy” sold by DOW Chemical Co., Ltd., and “TEPIC (registered trademark)” sold by Nissan Chemical Industries, Ltd.
[0065] On the other hand, alicyclic epoxy compounds having an epoxy group directly bonded to a saturated carbon ring can be produced, for example, by epoxidizing the CC double bond of a non-aromatic cyclic compound having a CC double bond in the ring using a peroxide under alkaline conditions. As non-aromatic cyclic compounds having a CC double bond in the ring, for example, compounds having a cyclopentene ring, compounds having a cyclohexene ring, polycyclic compounds having at least two carbon atoms bonded to the cyclopentene ring or the cyclohexene ring to form an additional ring, etc. can be cited. Non-aromatic cyclic compounds having a CC double bond in the ring may have other CC double bonds outside the ring. If examples of non-aromatic cyclic compounds having a CC double bond in the ring are cited, there are cyclohexene, 4-vinylcyclohexene, limonene as a monocyclic monoterpene, and α-pinene, etc.
[0066] The alicyclic epoxy compound having an epoxy group directly bonded to a saturated carbon ring may also be a compound having at least two alicyclic structures having epoxy groups directly bonded to the ring as described above formed in the molecule via an appropriate linking group. The linking group mentioned here includes, for example, an ester bond, an ether bond, an alkylene bond, etc.
[0067] If specific examples of the alicyclic epoxy compound in which an epoxy group is directly bonded to a saturated carbon ring are given, there are the following compounds.
[0068] 3,4-Epoxycyclohexyl methyl ester,
[0069] 1,2-Epoxy-4-vinylcyclohexane,
[0070] 1,2-Epoxy-4-epoxyethylcyclohexane,
[0071] 1,2-Epoxy-1-methyl-4-(1-methylepoxyethyl)cyclohexane,
[0072] (Meth)acrylate 3,4-epoxycyclohexyl methyl ester,
[0073] 2,2-bis(hydroxymethyl)-1-butanol and 4-epoxyethyl-1,2-epoxycyclohexane adduct,
[0074] Ethylene bis(3,4-epoxycyclohexanecarboxylate),
[0075] Oxydiethylenebis(3,4-epoxycyclohexanecarboxylate),
[0076] 1,4-cyclohexanedimethylbis(3,4-epoxycyclohexanecarboxylate),
[0077] 3,4-Epoxycyclohexanecarboxylic acid 3-(3,4-epoxycyclohexylmethoxycarbonyl)propyl ester, etc.
[0078] The alicyclic epoxy compounds in which an epoxy group is directly bonded to a saturated carbon ring as described above are also easily commercially available products, and examples thereof include the "Celoxide (registered trademark)" series and "Cyclomer (registered trademark)" series sold by Daicel Co., Ltd., and the "Cyracure UVR" series sold by DOW Chemical Co., Ltd.
[0079] The curable adhesive containing the epoxy compound may further contain an active energy ray curable compound other than the epoxy compound. As the active energy ray curable compound other than the epoxy compound, for example, an oxetane compound, an acrylic compound, etc. can be cited. Among them, since it is possible to promote the curing speed in cationic polymerization, it is preferred to use an oxetane compound in combination.
[0080] The oxetane compound is a compound having a four-membered cyclic ether in the molecule, and examples thereof include the following compounds.
[0081] 1,4-bis[(3-ethyloxetane-3-yl)methoxymethyl]benzene,
[0082] 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane,
[0083] Bis(3-ethyl-3-oxetanylmethyl)ether,
[0084] 3-ethyl-3-(phenoxymethyl)oxetane,
[0085] 3-ethyl-3-(cyclohexyloxymethyl)oxetane,
[0086] Phenol novolac oxetane,
[0087] Xylene dioxetane,
[0088] 1,3-Bis[(3-ethyloxetane-3-yl)methoxy]benzene, etc.
[0089] Oxetane compounds are also readily available as commercial products, and examples thereof include the “ARONOXETANE (registered trademark)” series sold by Toagosei Co., Ltd. and the “ETERNACOLL (registered trademark)” series sold by Ube Industries, Ltd.
[0090] For curable compounds including epoxy compounds and oxetane compounds, it is preferred to use curable compounds that have not been diluted with an organic solvent, etc., in order to make the adhesive containing them solvent-free. In addition, for other components constituting the adhesive, including a small amount of cationic polymerization initiator and sensitizer described later, it is more preferred to use a powder or liquid of the compound alone from which the organic solvent has been removed and dried, rather than a substance dissolved in an organic solvent.
[0091] Cationic polymerization initiators are compounds that generate cationic species after being irradiated with active energy rays, such as ultraviolet rays. Any cationic polymerization initiator that can impart the required bonding strength and curing speed to the adhesive in which it is formulated may be used, and examples thereof include aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts and other onium salts; iron-arene complexes, etc. These cationic polymerization initiators may be used alone or in combination of different types.
[0092] Examples of the aromatic diazonium salt include the following.
[0093] Benzenediazonium hexafluoroantimonate,
[0094] Benzenediazonium hexafluorophosphate,
[0095] Benzenediazonium hexafluoroborate, etc.
[0096] Examples of the aromatic iodonium salt include the following.
[0097] Diphenyliodonium tetrakis(pentafluorophenyl)borate,
[0098] Diphenyliodonium hexafluorophosphate,
[0099] Diphenyliodonium hexafluoroantimonate,
[0100] Bis(4-nonylphenyl)iodonium hexafluorophosphate, etc.
[0101] Examples of the aromatic sulfonium salt include the following.
[0102] Triphenylsulfonium hexafluorophosphate,
[0103] Triphenylsulfonium hexafluoroantimonate,
[0104] Triphenylsulfonium tetrakis(pentafluorophenyl)borate,
[0105] Diphenyl (4-phenylthiophenyl) sulfonium hexafluoroantimonate,
[0106] 4,4'-Bis(diphenylsulfonium)diphenyl sulfide bis(hexafluorophosphate),
[0107] 4,4'-bis[bis(β-hydroxyethoxyphenyl)sulfonium]diphenyl sulfide bis(hexafluoroantimonate),
[0108] 4,4'-bis[bis(β-hydroxyethoxyphenyl)sulfonium]diphenyl sulfide bis(hexafluorophosphate),
[0109] 7-[di(p-toluoyl)sulfonyl]-2-isopropylthioxanthone hexafluoroantimonate,
[0110] 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate,
[0111] 4-Phenylcarbonyl-4′-diphenylsulfonium diphenyl sulfide hexafluorophosphate,
[0112] 4-(p-tert-butylphenylcarbonyl)-4′-diphenylsulfonium diphenyl sulfide hexafluoroantimonate,
[0113] 4-(p-tert-butylphenylcarbonyl)-4′-di(p-toluoyl)sulfonium-diphenylsulfide tetrakis(pentafluorophenyl)borate, etc.
[0114] Examples of the iron-arene complex include the following.
[0115] Xylene-cyclopentadienyl iron (II) hexafluoroantimonate,
[0116] Isopropylbenzene-cyclopentadienyl iron (II) hexafluorophosphate,
[0117] Xylene-cyclopentadienylferrous(II)tris(trifluoromethanesulfonyl)methanide, etc.
[0118] Among cationic polymerization initiators, aromatic sulfonium salts have ultraviolet absorption properties even in the wavelength region of 300 nm or longer, and thus can provide an adhesive layer having excellent curability and good mechanical strength and adhesive strength, and are therefore preferably used.
[0119] Cationic polymerization initiators are also readily available commercially. Examples of the initiators include the “Kayarad (registered trademark)” series sold by Nippon Kayaku Co., Ltd., the “Cyracure UVI” series sold by DOW Chemical Co., Ltd., the “CPI” series of photoacid generators sold by San-Apro Co., Ltd., the photoacid generators “TAZ”, “BBI” and “DTS” sold by Midori Chemical Co., Ltd., the “Adeka Optomer” series sold by ADEKA Co., Ltd., and the “RHODORSIL (registered trademark)” sold by RHODIA Co., Ltd.
[0120] In the active energy ray-curable adhesive, the cationic polymerization initiator is usually mixed in a ratio of 0.5 to 20 parts by mass, preferably 1 to 15 parts by mass, relative to 100 parts by mass of the total amount of the active energy ray-curable adhesive. If the amount is too small, the curing becomes insufficient, and the mechanical strength and bonding strength of the adhesive layer may be reduced. In addition, if the amount is too large, the ionic substance in the adhesive layer increases, thereby increasing the hygroscopicity of the adhesive layer, and the durability of the resulting polarizing plate may be reduced.
[0121] When an active energy ray curable adhesive is used as an electron beam curable adhesive, it is not particularly necessary to contain a photopolymerization initiator in the composition, but when it is used as an ultraviolet curable adhesive, it is preferred to use a photoradical generator. Examples of the photoradical generator include hydrogen abstraction type photoradical generators and cleavage type photoradical generators.
[0122] Examples of the hydrogen abstraction type photoradical generator include 1-methylnaphthalene, 2-methylnaphthalene, 1-fluoronaphthalene, 1-chloronaphthalene, 2-chloronaphthalene, 1-bromonaphthalene, 2-bromonaphthalene, 1-iodonaphthalene, 2-iodonaphthalene, 1-naphthalene, 2-naphthalene, 1-methoxynaphthalene, 2-methoxynaphthalene, 1,4-dicyanonaphthalene and other naphthalene derivatives, anthracene, 1,2-benzanthracene, 9,10-dichloroanthracene, 9,10-dibromoanthracene, 9,10-diphenylanthracene, 9-cyanoanthracene, 9,10-dicyanoanthracene, 2,6,9,10-tetracyanoanthracene and other anthracene derivatives, pyrene derivatives, carbazole, 9-methylcarbazole, 9-phenylcarbazole, 9- Prop-2-enyl-9H-carbazole, 9-propyl-9H-carbazole, 9-vinyl carbazole, 9H-carbazole-9-ethanol, 9-methyl-3-nitro-9H-carbazole, 9-methyl-3,6-dinitro-9H-carbazole, 9-octanoyl carbazole, 9-carbazole methanol, 9-carbazole propionic acid, 9-carbazole propionitrile, 9-ethyl-3,6-dinitro-9H-carbazole, 9-ethyl-3-nitrocarbazole, 9-ethyl carbazole, 9-isopropyl carbazole, 9-(ethoxycarbonylmethyl) carbazole, 9-(morpholinylmethyl) carbazole, 9-acetyl carbazole, 9-allyl carbazole, 9-benzyl-9 H-carbazole, 9-carbazoleacetic acid, 9-(2-nitrophenyl)carbazole, 9-(4-methoxyphenyl)carbazole, 9-(1-ethoxy-2-methyl-propyl)-9H-carbazole, 3-nitrocarbazole, 4-hydroxycarbazole, 3,6-dinitro-9H-carbazole, 3,6-diphenyl-9H-carbazole, 2-hydroxycarbazole, 3,6-diacetyl-9-ethylcarbazole and other carbazole derivatives, benzophenone, 4-phenylbenzophenone, 4,4'-bis(dimethoxy)benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, Benzophenone derivatives such as 2-benzoylbenzoic acid methyl ester, 2-methylbenzophenone, 3-methylbenzophenone, 4-methylbenzophenone, 3,3'-dimethyl-4-methoxybenzophenone, 2,4,6-trimethylbenzophenone, aromatic carbonyl compounds, [4-(4-methylphenylthio)phenyl]-phenyl ketone, xanthone, thioxanthone, 2-chlorothioxanthone, 4-chlorothioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 1-chloro-4-propoxythioxanthone, and coumarin derivatives.
[0123] The cleavage-type photo-radical generator is a type of photo-radical generator that cleaves the compound and generates free radicals by irradiating it with active energy rays. Specific examples thereof include aryl alkyl ketones such as benzoin ether derivatives and acetophenone derivatives, oxime ketones, acyl phosphine oxides, S-phenylthiobenzoate, titanocene, and derivatives thereof obtained by making them high in molecular weight, but are not limited to these. Examples of commercially available cleavage-type photoradical generators include 1-(4-dodecylbenzoyl)-1-hydroxy-1-methylethane, 1-(4-isopropylbenzoyl)-1-hydroxy-1-methylethane, 1-benzoyl-1-hydroxy-1-methylethane, 1-[4-(2-hydroxyethoxy)-benzoyl]-1-hydroxy-1-methylethane, 1-[4-(acryloyloxyethoxy)-benzoyl]-1-hydroxy-1-methylethane, diphenyl ketone, phenyl-1-hydroxy-cyclohexyl ketone, benzyl dimethyl ketal, bis(cyclopentadienyl)-bis(2,6-difluoro-3- The present invention also includes bis(2,6-dimethoxybenzoyl)-(2,4,4-trimethyl-pentyl)-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-dipentyloxyphenylphosphine oxide or bis(2,4,6-trimethylbenzoyl)phenyl-phosphine oxide, (4-morpholinobenzoyl)-1-benzyl-1-dimethylaminopropane, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, etc., but is not limited thereto.
[0124] In the active energy curing adhesive used in the present invention, the photoradical generator contained in the electron beam curing type, that is, the hydrogen abstraction type or the cleavage type photoradical generator, can be used alone or in combination. However, from the perspective of the stability and curability of the photoradical generator alone, a combination of more than one cleavage type photoradical generator is more preferred. Among the cleavage type photoradical generators, acylphosphine oxides are preferred, and more specifically, trimethylbenzoyldiphenylphosphine oxide (trade name "DAROCURE TPO"; Ciba Japan (Strain)), bis(2,6-dimethoxy-benzoyl)-(2,4,4-trimethyl-pentyl)-phosphine oxide (trade name "CGI 403"; Ciba Japan (Strain)), or bis(2,4,6-trimethylbenzoyl)-2,4-dipentyloxyphenylphosphine oxide (trade name "Irgacure 819"; Ciba Japan (Strain)) is preferred.
[0125] The active energy ray-curable adhesive may contain a sensitizer as required. By using a sensitizer, the reactivity can be improved, and the mechanical strength and bonding strength of the adhesive layer can be further improved. As the sensitizer, the above-mentioned sensitizers can be appropriately used.
[0126] When a sensitizer is added, the amount thereof added is preferably in the range of 0.1 to 20 parts by mass based on 100 parts by mass of the total amount of the active energy ray-curable adhesive.
[0127] Various additives may be added to the active energy ray-curable adhesive within a range that does not impair its effect. Examples of additives that may be added include ion trapping agents, antioxidants, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, and the like.
[0128] These components constituting the active energy ray-curable adhesive are usually used in a state of being dissolved in a solvent. When the active energy ray-curable adhesive contains a solvent, the adhesive layer is obtained by applying the active energy ray-curable adhesive to the coating surface and drying it. The components insoluble in the solvent can be dispersed in the system.
[0129] The active energy ray curing adhesive is applied to the bonding surface of the 1 / 2 wavelength layer 11 and the 1 / 4 wavelength layer 12, the bonding surface of the 1 / 4 wavelength layer 12 and the 1 / 2 wavelength layer 11, or both. The bonding surface of the 1 / 2 wavelength layer 11 and the bonding surface of the 1 / 4 wavelength layer 12 and the bonding surface of the 1 / 4 wavelength layer 12 and the 1 / 2 wavelength layer 11 may be pre-corona treated, plasma treated, flame treated, etc., and a primer layer may also be formed. The thickness of the primer layer is generally about 0.001 to 5 μm, preferably more than 0.01 μm, and preferably less than 4 μm, more preferably less than 3 μm. If the primer layer is too thick, it is easy to cause a poor appearance of the composite phase difference plate 5.
[0130] As for the viscosity of the active energy ray curing adhesive, any adhesive having a viscosity that can be applied by various methods is sufficient, and the viscosity at a temperature of 25° C. is preferably in the range of 10 to 1000 mPa·sec, and more preferably in the range of 20 to 500 mPa·sec. If the viscosity is too low, it tends to be difficult to form a layer of the desired thickness. On the other hand, if the viscosity is too high, it tends to be difficult to flow, and it tends to be difficult to obtain a uniform coating without unevenness. The viscosity referred to here is a value measured at 10 rpm after the adhesive is adjusted to 25° C. using an E-type viscometer.
[0131] The above-mentioned active energy ray curing adhesive can be used in the form of electron beam curing type and ultraviolet curing type. In this specification, the so-called active energy ray is defined as an energy ray that can decompose a compound that generates active species to generate active species. Examples of such active energy rays include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams.
[0132] In the electron beam curing type, the irradiation conditions of the electron beam can be any appropriate conditions as long as they are conditions that can cure the above-mentioned active energy ray-curing adhesive. For example, the acceleration voltage of the electron beam irradiation is preferably 5kV to 300kV, and more preferably 10kV to 250kV. When the acceleration voltage is less than 5kV, the electron beam cannot reach the adhesive, which may lead to insufficient curing. If the acceleration voltage is greater than 300kV, the penetration force through the sample is too strong and the electron beam rebounds, which may cause damage to the transparent protective film and polarizer. As an irradiation dose, it is preferably 5 to 100kGy, and more preferably 10 to 75kGy. When the irradiation dose is less than 5kGy, the adhesive is not sufficiently cured. If it is greater than 100kGy, the phase difference layer is damaged, resulting in a reduction in mechanical strength and yellowing, and the desired optical properties cannot be obtained.
[0133] Electron beam irradiation is usually performed in an inert gas, but it can be performed in the air or under the condition of introducing a small amount of oxygen if necessary. By introducing oxygen appropriately, oxygen barrier is generated on the surface of the phase difference layer that the electron beam hits first, which can prevent damage to the phase difference layer and allow the electron beam to effectively irradiate only the adhesive.
[0134] In the case of ultraviolet curing type, the light irradiation intensity of the active energy ray curing adhesive is determined according to each composition of the adhesive and is not particularly limited, but is preferably 10 to 1000 mW / cm 2 If the light intensity of the resin composition is less than 10mW / cm 2 If it is greater than 1000mW / cm 2 , the heat radiated from the light source and the heat generated during the polymerization of the composition may cause yellowing of the constituent materials of the adhesive. It should be noted that the irradiation intensity is preferably an intensity in the wavelength region effective for the activation of the photocationic polymerization initiator, more preferably an intensity in the wavelength region below 400nm, and further preferably an intensity in the wavelength region of 280 to 320nm. The irradiation is performed once or multiple times with such light irradiation intensity, preferably to a temperature of 10mJ / cm 2 More preferably, 100 to 1000 mJ / cm 2 If the cumulative light intensity of the adhesive is less than 10mJ / cm2 On the other hand, if the cumulative light intensity is greater than 1000 mJ / cm 2 , the irradiation time is very long, which is not conducive to improving productivity. At this time, the required wavelength region (UVA (320-390nm), UVB (280-320nm) etc.) of the integrated light amount varies depending on the type of film used for the phase difference layer, the combination of the type of adhesive, etc.
[0135] The light source used in the present invention for polymerizing and curing the adhesive by irradiation with active energy rays is not particularly limited, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380 to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps. From the viewpoint of energy stability and simplicity of the device, an ultraviolet light source having a light emission distribution of less than 400 nm in wavelength is preferred.
[0136] <1 / 2 wavelength layer, 1 / 4 wavelength layer>
[0137] As long as the 1 / 2 wavelength layer 11 and the 1 / 4 wavelength layer 12 are wavelength layers including at least one phase difference display layer, they can be formed only by the phase difference display layer, or they can also include other layers together with the phase difference display layer. As other layers, for example, a substrate layer, an orientation film layer, a protective layer, etc. can be cited. It should be noted that other layers do not affect the value of the phase difference. In addition, regardless of whether there are other layers, in this specification, the refractive index of the phase difference layer refers to the refractive index of the phase difference display layer.
[0138] As the phase difference display layer, there can be cited a layer formed by using a liquid crystal compound (hereinafter referred to as a "liquid crystal layer") or a stretched film. From the viewpoint of thinning the polarizing plate complex, the phase difference display layer is preferably a liquid crystal layer. The phase difference display layer as a liquid crystal layer is generally easier to thin film than the phase difference display layer as a stretched film. The thickness of the phase difference display layer is preferably 0.5μm to 10μm, and more preferably 0.5μm to 5μm. It should be noted that when the 1 / 2 wavelength layer 11 and the 1 / 4 wavelength layer 12 include other layers (substrate layer, orientation film layer, protective layer, etc.) other than the phase difference display layer, the overall thickness is preferably 0.5μm to 300μm, and more preferably 0.5μm to 150μm.
[0139] The optical properties of the phase difference layer can be adjusted by the alignment state of the liquid crystal compound constituting the phase difference showing layer or the stretching method of the stretched film constituting the phase difference showing layer.
[0140] (1 / 2 wavelength layer)
[0141] The half-wavelength layer 11 has the function of changing the direction (polarization azimuth) of linear polarization by giving a phase difference of π (=λ / 2) to the electric field vibration direction (polarization plane) of incident light. In addition, if circularly polarized light is incident, the rotation direction of the circularly polarized light can be reversed.
[0142] The 1 / 2 wavelength layer 11 is a layer in which Re(λ) as an in-plane retardation value at a specific wavelength λnm satisfies Re(λ)=λ / 2. Although Re(λ)=λ / 2 can be achieved at any wavelength in the visible light region, it is preferably achieved at a wavelength of 550nm. Re(550) as an in-plane retardation value at a wavelength of 550nm preferably satisfies 210nm≤Re(550)≤300nm. In addition, it is more preferable to satisfy 220nm≤Re(550)≤290nm.
[0143] The refractive index of the 1 / 2 wavelength layer 11 in the fast axis direction at a wavelength of 589 nm (n11 y ) is preferably less than 1.60, more preferably less than 1.59.
[0144] (1 / 4 wavelength layer)
[0145] The quarter wavelength layer 12 provides a phase difference of π / 2 (=λ / 4) to the electric field vibration direction (polarization plane) of incident light, and has the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or converting circularly polarized light into linearly polarized light).
[0146] The 1 / 4 wavelength layer 12 is a layer in which Re(λ) as an in-plane retardation value at a specific wavelength λnm satisfies Re(λ)=λ / 4, and although it can be achieved at any wavelength in the visible light region, it is preferably achieved at a wavelength of 550nm. Re(550) as an in-plane retardation value at a wavelength of 550nm preferably satisfies 100nm≤Re(550)≤160nm. In addition, it is more preferable to satisfy 110nm≤Re(550)≤150nm.
[0147] The average refractive index of the quarter wavelength layer 12 at a wavelength of 589 nm (n12 x,y ) is preferably less than 1.58, more preferably less than 1.57.
[0148] (Phase difference display layer formed by liquid crystal layer)
[0149] The case where the phase difference display layer of the phase difference layer is a liquid crystal layer will be described. The phase difference layer may be a 1 / 2 wavelength layer or a 1 / 4 wavelength layer. Figure 2 2 is a schematic cross-sectional view schematically showing an example of a phase difference layer including a phase difference display layer as a liquid crystal layer and other layers. Figure 2 As shown in FIG. 1 , the phase difference layer 30 is formed by sequentially stacking a substrate layer 31, an orientation layer 32, and a phase difference display layer 33 as a liquid crystal layer. The phase difference layer is not limited to any structure as long as it includes the phase difference display layer 33 as a liquid crystal layer. Figure 2 The phase difference layer 30 shown may be a structure in which the substrate layer 31 is peeled off from the phase difference layer 30 and only the orientation layer 32 and the phase difference display layer 33 are formed, or may be a structure in which the substrate layer 31 and the orientation layer 32 are peeled off from the phase difference layer 30 and only the phase difference display layer 33 as a liquid crystal layer is formed. From the viewpoint of thin film, the phase difference layer is preferably a structure in which the substrate layer 31 is peeled off, and more preferably a structure in which only the phase difference display layer 33 as a liquid crystal layer is formed. The substrate layer 31 functions as a supporting layer for supporting the orientation layer 32 formed on the substrate layer 31 and the phase difference display layer 33 as a liquid crystal layer. The substrate layer 31 is preferably a film formed of a resin material.
[0150] As the resin material, for example, a resin material having excellent transparency, mechanical strength, thermal stability, stretchability, etc. can be used. Specifically, polyolefin resins such as polyethylene and polypropylene; cyclic polyolefin resins such as norbornene polymers; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; (meth) acrylic acid resins such as (meth) acrylic acid and poly (meth) methyl acrylate; cellulose ester resins such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; vinyl alcohol resins such as polyvinyl alcohol and polyvinyl acetate; polycarbonate resins; polystyrene resins; polyarylate resins; polysulfone resins; polyethersulfone resins; polyamide resins; polyimide resins; polyetherketone resins; polyphenylene sulfide resins; polyphenylene ether resins, and mixtures and copolymers thereof can be cited. Among these resins, any one of cyclic polyolefin resins, polyester resins, cellulose ester resins and (meth) acrylic resins or mixtures thereof is preferably used. In addition, the above-mentioned "(meth)acrylic acid" means "at least one of acrylic acid and methacrylic acid".
[0151] The base material layer 31 may be a single layer of one or a mixture of two or more of the above-mentioned resins, or may have a multilayer structure of two or more layers. In the case of a multilayer structure, the resins forming each layer may be the same or different.
[0152] The resin material for forming the resin film may be added with optional additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0153] The thickness of the base material layer 31 is not particularly limited, but is usually preferably 5 to 200 μm, more preferably 10 to 200 μm, and even more preferably 10 to 150 μm from the viewpoint of strength, handling properties, and the like.
[0154] In order to improve the adhesion between the substrate layer 31 and the orientation layer 32, at least the surface of the substrate layer 31 on the side where the orientation layer 32 is formed may be subjected to corona treatment, plasma treatment, flame treatment, etc., or a primer layer may be formed. It should be noted that when the substrate layer 31, or the substrate layer 31 and the orientation layer 32 are peeled off to form a phase difference layer, peeling can be facilitated by adjusting the adhesion at the peeling interface.
[0155] The alignment layer 32 has an alignment restraining force that causes the liquid crystal compound contained in the phase difference display layer 33 as a liquid crystal layer formed on the alignment layer 32 to be aligned in a desired direction. Examples of the alignment layer 32 include an alignment polymer layer formed of an alignment polymer, a photoalignment polymer layer formed of a photoalignment polymer, and a groove alignment layer having a concave-convex pattern and a plurality of grooves on the surface of the layer. The thickness of the alignment layer 32 is usually 0.01 to 10 μm, preferably 0.01 to 5 μm.
[0156] The composition in which the oriented polymer is dissolved in the solvent is applied to the base material layer 31 and the solvent is removed, and a rubbing treatment is performed as needed to form an oriented polymer layer. In this case, the orientation restriction force can be arbitrarily adjusted in the oriented polymer layer formed by the oriented polymer by utilizing the surface state of the oriented polymer and the rubbing conditions.
[0157] The photo-aligned polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to the base layer 31 and irradiating the base layer with polarized light. In this case, the alignment regulating force in the photo-aligned polymer layer can be arbitrarily adjusted by, for example, irradiating the photo-aligned polymer with polarized light.
[0158] The groove orientation layer can be formed, for example, by the following methods, namely, a method of exposing and developing a concave-convex pattern on the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape; a method of forming an uncured layer of an active energy ray-curable resin on a plate-shaped original disk having grooves on the surface, transferring the layer to a substrate layer 31 and curing the layer; a method of forming an uncured layer of an active energy ray-curable resin on a substrate layer 31, and curing the layer by pressing a roller-shaped original disk having grooves to the layer to form the grooves.
[0159] The phase difference display layer 33 as a liquid crystal layer provides a predetermined phase difference to light, and examples thereof include a phase difference display layer for a half wavelength layer and a phase difference display layer for a quarter wavelength layer.
[0160] The phase difference display layer 33 as a liquid crystal layer can be formed using a known liquid crystal compound. The type of liquid crystal compound is not particularly limited, and a rod-shaped liquid crystal compound, a disc-shaped liquid crystal compound, and a mixture thereof can be used. In addition, the liquid crystal compound can be a polymer liquid crystal compound, a polymerizable liquid crystal compound, or a mixture thereof. Examples of the liquid crystal compound include liquid crystal compounds described in JP-A-11-513019, JP-A-2005-289980, JP-A-2007-108732, JP-A-2010-244038, JP-A-2010-31223, JP-A-2010-270108, JP-A-2011-6360, JP-A-2011-207765, JP-A-2016-81035, International Publication No. 2017 / 043438, and JP-A-2011-207765.
[0161] For example, when a polymerizable liquid crystal compound is used, a composition containing the polymerizable liquid crystal compound is applied on the alignment layer 32 to form a coating film, and the coating film is cured to form the phase difference display layer 33. The thickness of the phase difference display layer 33 is preferably 0.5 μm to 10 μm, more preferably 0.5 to 5 μm.
[0162] The composition containing the polymerizable liquid crystal compound may contain a polymerization initiator, a polymerizable monomer, a surfactant, a solvent, a close contact improver, a plasticizer, an alignment agent, etc. in addition to the liquid crystal compound. As a coating method for the composition containing the polymerizable liquid crystal compound, a known method such as a die coating method can be cited. As a curing method for the composition containing the polymerizable liquid crystal compound, a known method such as irradiation with active energy rays (such as ultraviolet rays) can be cited.
[0163] (Phase difference layer having a stretched film as a phase difference showing layer)
[0164] The case where the phase difference showing layer is a stretched film is described. The stretched film is usually obtained by stretching a substrate. As a method for stretching the substrate, for example, a roll (winding body) in which the substrate is wound in a roll shape is prepared, the substrate is continuously rolled out from the winding body, and the rolled-out substrate is transported to a heating furnace. The set temperature of the heating furnace is set to a range of near the glass transition temperature of the substrate (°C) to [glass transition temperature + 100] (°C), preferably set to a range of near the glass transition temperature (°C) to [glass transition temperature + 50] (°C). In the heating furnace, when stretching in the direction of travel of the substrate or in a direction orthogonal to the direction of travel, the conveying direction and tension are adjusted to perform uniaxial or biaxial heat stretching treatment at an angle of any angle. The stretching ratio is usually 1.1 to 6 times, preferably 1.1 to 3.5 times.
[0165] In addition, as a method for stretching in an oblique direction, as long as it is a method that can continuously tilt the orientation axis along a desired angle, it is not particularly limited, and a known stretching method can be adopted. Such a stretching method can, for example, be cited the method described in Japanese Patent Laid-Open No. 50-83482 and Japanese Patent Laid-Open No. 2-113920. In the case of imparting phase difference to the film by stretching, the thickness after stretching is determined according to the thickness before stretching and the stretching ratio.
[0166] The substrate is usually a transparent substrate. The so-called transparent substrate refers to a transparent substrate that can transmit light, especially visible light, and the so-called transparency refers to the property that the transmittance of light with a wavelength of 380 to 780 nm is 80% or more. As a specific transparent substrate, a translucent resin substrate can be cited. As the resin constituting the translucent resin substrate, polyolefins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether. From the viewpoint of ease of acquisition and transparency, polyethylene terephthalate, polymethacrylate, cellulose ester, cyclic olefin resin or polycarbonate is preferred.
[0167] Cellulose ester is a substance in which a part or all of the hydroxyl groups contained in cellulose are esterified, and it can be easily obtained from the market. In addition, cellulose ester substrates can also be easily obtained from the market. Examples of commercially available cellulose ester substrates include "FUJITAC (registered trademark) Film" (Fuji Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (Konica Minolta Opto Co., Ltd.), etc.
[0168] Polymethacrylate and polyacrylate (hereinafter, polymethacrylate and polyacrylate may be collectively referred to as (meth)acrylic resin) are easily available on the market.
[0169] As the (meth)acrylic resin, for example, homopolymers of alkyl methacrylate or alkyl acrylate, copolymers of alkyl methacrylate and alkyl acrylate, etc. can be cited. As the alkyl methacrylate, specifically, methyl methacrylate, ethyl methacrylate, propyl methacrylate, etc. can be cited. As the alkyl acrylate, specifically, methyl acrylate, ethyl acrylate, propyl acrylate, etc. can be cited. As the (meth)acrylic resin, a resin sold as a general-purpose (meth)acrylic resin can be used. As the (meth)acrylic resin, a resin called an impact-resistant (meth)acrylic resin can also be used.
[0170] In order to further improve the mechanical strength, it is also preferred to contain rubber particles in the (meth)acrylic resin. The rubber particles are preferably acrylic rubber particles. Here, the so-called acrylic rubber particles are particles with rubber elasticity obtained by polymerizing acrylic monomers with acrylic acid alkyl esters such as butyl acrylate and 2-ethylhexyl acrylate as the main component in the presence of a multifunctional monomer. The acrylic rubber particles can be a material that forms such particles with rubber elasticity in a single layer, or a multilayer structure having at least one rubber elastic layer. As multilayer acrylic rubber particles, there can be cited: particles with the above-mentioned rubber elastic particles as the core and the surroundings covered with a hard methacrylate alkyl ester polymer; particles with a hard methacrylate alkyl ester polymer as the core and the surroundings covered with the above-mentioned rubber elastic acrylic polymer; and particles with the surroundings of the hard core covered with a rubber elastic acrylic polymer and the surroundings covered with a hard methacrylate alkyl ester polymer. The average diameter of the rubber particles formed by the elastic layer is usually in the range of about 50 to 400 nm.
[0171] The content of rubber particles in the (meth)acrylic resin is generally about 5 to 50 parts by mass per 100 parts by mass of the (meth)acrylic resin. Since the (meth)acrylic resin and the acrylic rubber particles are sold in a mixed state, commercial products thereof can be used. Examples of commercial products of (meth)acrylic resins with acrylic rubber particles include "HT55X" and "Technoloy S001" sold by Sumitomo Chemical Co., Ltd. "Technoloy S001" is sold in the form of a film.
[0172] Cyclic olefin resins can be easily obtained from the market. Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) [Ticona (Germany)], "Arton" (registered trademark) [JSR (Strain)], "ZEONOR" (registered trademark) [ZEON (Japan)], "ZEONEX" (registered trademark) [ZEON (Japan)], and "APEL" (registered trademark) [Mitsui Chemicals (Million)]. Such cyclic olefin resins can be made into films by known methods such as solvent casting and melt extrusion to form a substrate. In addition, commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include "ESCENA" (registered trademark) [Sekisui Chemical Co., Ltd.], "SCA40" (registered trademark) [Sekisui Chemical Co., Ltd.], "ZEONOR Film" (registered trademark) [OPTES (Strain)], and "Arton Film" (registered trademark) [JSR (Strain)].
[0173] In the case where the cyclic olefin resin is a copolymer of a cyclic olefin, a chain olefin, and an aromatic compound having a vinyl group, the content ratio of the structural unit derived from the cyclic olefin is generally 50 mol% or less, preferably in the range of 15 to 50 mol%, relative to the total structural units of the copolymer. As chain olefins, ethylene and propylene can be cited, and as aromatic compounds having a vinyl group, styrene, α-methylstyrene, and alkyl-substituted styrene can be cited. In the case where the cyclic olefin resin is a terpolymer of a cyclic olefin, a chain olefin, and an aromatic compound having a vinyl group, the content ratio of the structural unit derived from the chain olefin is generally 5 to 80 mol% relative to the total structural units of the copolymer, and the content ratio of the structural unit derived from the aromatic compound having a vinyl group is generally 5 to 80 mol% relative to the total structural units of the copolymer. This terpolymer has the advantage that less expensive cyclic olefins can be used in its manufacture.
[0174] <Linear polarizing plate>
[0175] The linear polarizing plate 13 can be any film having a polarization function of obtaining linear polarized light from transmitted light. As the film, a stretched film adsorbed with a pigment having absorption anisotropy or a film containing a film coated with a pigment having absorption anisotropy as a polarizer, etc. can be cited. As a pigment having absorption anisotropy, for example, a dichroic pigment can be cited. As a film used as a polarizer, a film coated with a pigment having absorption anisotropy, a stretched film adsorbed with a pigment having absorption anisotropy or a film having a liquid crystal layer obtained by coating a composition containing a dichroic pigment having liquid crystal or a composition containing a dichroic pigment and polymerizable liquid crystal, etc. can be cited.
[0176] (Linear polarizing plate with stretched film as polarizer)
[0177] A linear polarizing plate having a stretched film adsorbed with a pigment having absorption anisotropy as a polarizer is described. The stretched film adsorbed with a pigment having absorption anisotropy as a polarizer is usually manufactured through the following steps, i.e., a step of uniaxially stretching a polyvinyl alcohol-based resin film, a step of adsorbing the dichroic pigment by dyeing the polyvinyl alcohol-based resin film with a dichroic pigment, a step of treating the polyvinyl alcohol-based resin film adsorbed with the dichroic pigment with an aqueous boric acid solution, and a step of washing with water after the treatment with the aqueous boric acid solution. The polarizer can be used directly as a linear polarizing plate, or a polarizing plate with a transparent protective film attached to at least one surface of the polarizer can be used as a linear polarizing plate.
[0178] The thickness of the polarizing plate obtained by uniaxially stretching the polyvinyl alcohol-based resin film, dyeing it with a dichroic dye, treating it with boric acid, washing it with water, and drying it is preferably 5 to 40 μm.
[0179] The material of the protective film attached to one or both sides of the polarizer is not particularly limited, and for example, cyclic polyolefin resin films, cellulose acetate resin films containing resins such as triacetyl cellulose and diacetyl cellulose, polyester resin films containing resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate resin films, (meth) acrylic resin films, polypropylene resin films, and other films known in the field. For the thickness of the protective film, from the perspective of thinning, it is usually 300 μm or less, preferably 200 μm or less, and more preferably 50 μm or less. In addition, it is usually 5 μm or more, preferably 20 μm or more. In addition, the protective film on the visible side may have a phase difference or may not have a phase difference. On the other hand, the phase difference of the protective film on the side stacked with the 1 / 2 wavelength layer 11 is preferably 10 nm or less.
[0180] (Linear polarizing plate having a film having a liquid crystal layer as a polarizer)
[0181] The linear polarizing plate having a film with a liquid crystal layer as a polarizer is described. As a film used as a polarizer, coated with a pigment having absorption anisotropy, a film obtained by coating a composition containing a dichroic pigment with liquid crystal properties or a composition containing a dichroic pigment and a liquid crystal compound, etc. can be cited. The film can be used alone as a linear polarizing plate, or it can be used as a linear polarizing plate with a protective film on one or both sides. As the protective film, the same protective film as the linear polarizing plate having a stretched film as a polarizer can be cited.
[0182] The film coated with the dye having absorption anisotropy is preferably thin, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 μm or more and 3 μm or less.
[0183] Specific examples of the film coated with a dye having absorption anisotropy include films described in Japanese Unexamined Patent Application Publication No. 2012-33249 and the like.
[0184] The above-mentioned dye having absorption anisotropy may be directly applied to the half-wavelength layer 11 to form a polarizing plate composite. In this case, the second adhesive layer 22 does not need to be provided.
[0185] <Second adhesive layer>
[0186] The second adhesive layer 22 may be formed of, for example, an adhesive, a water-based adhesive, an active energy ray-curable adhesive, or a combination thereof. In this specification, the term "second adhesive layer" includes not only an adhesive layer formed of an adhesive but also an adhesive layer formed of an adhesive.
[0187] The description of the first adhesive layer 21 is applicable to the active energy ray-curable adhesive forming the second adhesive layer 22. When the first adhesive layer 21 and the second adhesive layer 22 are formed of an active energy ray-curable adhesive, the first adhesive layer 21 and the second adhesive layer 22 may be formed of the same active energy ray-curable adhesive or different active energy ray-curable adhesives. The refractive index n22 of the second adhesive layer 22 at a wavelength of 589 nm is preferably less than 1.55.
[0188] <Other floors>
[0189] The polarizing plate composite may have layers other than those described above. For example, it may have a phase difference layer for optical compensation, or it may have a third adhesive layer other than the first adhesive layer 21 and the second adhesive layer 22. The third adhesive layer is, for example, an adhesive layer provided on the surface of the quarter wavelength layer 12 on the opposite side to the first adhesive layer 21, and may be used to bond the polarizing plate composite to the image display panel.
[0190] [Method for producing a polarizing plate composite]
[0191] Figure 3 (A) to (D) are schematic cross-sectional views schematically showing an example of a method for producing a polarizing plate composite of the present invention. Figure 3 The half-wavelength layer 11 shown in (A) includes the first phase difference showing layer 113, the first orientation layer 112 and the first base layer 111, and Figure 3The quarter-wave layer 12 including the second phase difference showing layer 123, the second orientation layer 122 and the first substrate layer 121 shown in (B) is laminated via the first adhesive layer 21 to obtain a composite phase difference plate 40. The composite phase difference plate 40 is, for example, Figure 3 As shown in (C), a laminated body is formed by laminating the first substrate layer 111, the first orientation layer 112, the first phase difference display layer 113, the first adhesive layer 21, the second phase difference display layer 123, the second orientation layer 122, and the second substrate layer 121 in this order. Figure 3 As shown in (D), the linear polarizing plate 13 is laminated on the half-wavelength layer 11 side via the second adhesive layer 22 to obtain a polarizing plate composite 10 .
[0192] The 1 / 2 wavelength layer 11 and the 1 / 4 wavelength layer 12 may be arranged so that the phase difference showing layers 113 and 123 are located inside, or may be arranged so that the phase difference showing layers 113 and 123 are located outside, but it is preferred that the phase difference showing layers 113 and 123 are arranged as follows: Figure 3 As shown in (C) and (D), the phase difference showing layers 113 and 123 are located inside each other and are arranged in contact with the first adhesive layer 21 .
[0193] As a method for bonding the half wavelength layer 11 and the quarter wavelength layer 12, there can be mentioned a method in which an active energy ray-curable adhesive constituting the first adhesive layer 21 is applied to either or both of the bonding surfaces of the half wavelength layer 11 and the quarter wavelength layer 12, and one is laminated on the bonding surface of the other, and then the adhesive is cured by irradiating active energy rays from the half wavelength layer 11 or the quarter wavelength layer 12 side. When applying the adhesive constituting the first adhesive layer 21, various coating methods such as a doctor blade, a wire rod, a die coater, a comma-type knife coater, and a gravure coater can be used.
[0194] The bonding surface of the half-wavelength layer 11 or the bonding surface of the quarter-wavelength layer 12 may be subjected to corona treatment, plasma treatment, or the like, or a primer layer may be formed.
[0195] The composite phase difference plate 40 may be Figure 3 The laminate shown in (C) may be a laminate obtained by peeling at least one of the first substrate layer 111 and the second substrate layer 121. Figure 3 The laminate shown in (C) is obtained by peeling off the first base layer 111 and the first orientation layer 112, or it can be Figure 3 The laminate shown in (C) is a laminate obtained by peeling the second base layer 121 and the second orientation layer 122 . Figure 4 Specific examples are given in (A) and (B).
[0196] Figure 4(A) and (B) are schematic representations of Figure 3 (C) is a schematic cross-sectional view of another example of a method for manufacturing a composite polarizing plate. Figure 4 (A) shows that from Figure 3 The composite phase difference plate 40 shown in (C) is obtained by peeling off the first substrate layer 111 and the first orientation layer 112, the second substrate layer 121 and the second orientation layer 122 to obtain a composite phase difference plate 40'. Figure 4 As shown in (B), the linear polarizing plate 13 is laminated on the half-wavelength layer 11 (first phase difference showing layer 113 ) side via the second adhesive layer 22 to obtain a polarizing plate composite 10 .
[0197] [Application of polarizing plate composite]
[0198] The polarizing plate complex belonging to the circular polarizing plate can be arranged on the visible side of the image display panel and used as an optical laminate with anti-reflection performance in various image display devices. The so-called image display device is a device having an image display panel, including a light-emitting element or a light-emitting device as a light source. As an image display device, a liquid crystal display device, an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (such as a field emission display device (FED), a surface field emission display device (SED)), an electronic paper (a display device using electronic ink and an electrophoretic element), a plasma display device, a projection display device (such as a grating light valve (GLV) display device, a display device with a digital micromirror device (DMD)) and a piezoelectric ceramic display can be cited. The liquid crystal display device also includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device and a projection liquid crystal display device. These image display devices can be image display devices that display two-dimensional images, or they can be stereoscopic image display devices that display three-dimensional images. In particular, the optical laminated body which is a circular polarizing plate can be effectively used in an organic electroluminescent (EL) display device which can include an image display panel having a curved portion.
[0199] Example
[0200] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. The amounts used and the contents expressed in parts and % are by mass unless otherwise specified.
[0201] [Adjustment of active energy ray-curable adhesive]
[0202] The following components were mixed at the mixing ratios (parts by mass) shown in Table 1 and degassed to prepare adhesives A to F. The cationic polymerization initiator (B) was mixed as a 50 mass % propylene carbonate solution, and Table 1 shows the solid content thereof.
[0203] (Epoxides)
[0204] A-1: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation)
[0205] A-2: Bisphenol F type epoxy resin (trade name: EXA-830CRP, manufactured by DIC Corporation)
[0206] A-3: Fluorene-based epoxy resin (trade name: OGSOL EG-200, manufactured by Osaka Gas Chemicals Co., Ltd.)
[0207] A-4: DCPDM type epoxy resin (trade name: EP-4088S, manufactured by ADEKA Corporation)
[0208] A-5: Neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Co., Ltd.)
[0209] A-6: Biphenyl type epoxy resin (trade name: EX-142, manufactured by Nagase ChemteX Co., Ltd.)
[0210] A-7: 2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Co., Ltd.)
[0211] (Initiator)
[0212] B: Cationic polymerization initiator (trade name: CPI-100P, manufactured by San-Apro Co., Ltd., 50 mass % solution)
[0213]
[0214] (Refractive index measurement method)
[0215] The adhesive prepared above was applied to one side of a stretched norbornene-based resin film [ZEONOR Film, manufactured by ZEON Corporation] using a bar coater [manufactured by Daiichi Rika Co., Ltd.], and then irradiated with an ultraviolet irradiation device [manufactured by Fusion UV Systems Co., Ltd.] at a cumulative light dose of 600 mJ / cm 2 (UV-B) UV rays were irradiated to obtain a cured product. The film thickness of the obtained cured product was about 30 μm.
[0216] The norbornene-based resin film was peeled off from the obtained cured product, and the refractive index (589 nm) of the cured product layer was measured using a multi-wavelength Abbe refractometer [“DR-M2” manufactured by ATAGO Corporation] at 25° C. The results are shown in Table 1.
[0217] [Manufacturing of polarizing plates]
[0218] After immersing a polyvinyl alcohol film having an average degree of polymerization of about 2400, a saponification degree of 99.9 mol% or more and a thickness of 75 μm in pure water at 30° C., the film was immersed in an aqueous solution having a mass ratio of iodine / potassium iodide / water of 0.02 / 2 / 100 at 30° C. to perform iodine dyeing (iodine dyeing step). The polyvinyl alcohol film that had undergone the iodine dyeing step was immersed in an aqueous solution having a mass ratio of potassium iodide / boric acid / water of 12 / 5 / 100 at 56.5° C. to perform boric acid treatment (boric acid treatment step).
[0219] The polyvinyl alcohol film after the boric acid treatment step was washed with pure water at 8°C and dried at 65°C to obtain a polarizer in which iodine was adsorbed and oriented in the polyvinyl alcohol. At this time, stretching was performed in the iodine dyeing step and the boric acid treatment step. The total stretching ratio in the stretching was 5.3 times, and the thickness of the obtained polarizer was 27 μm.
[0220] A saponified triacetyl cellulose film (trade name: KC4UYTAC, manufactured by Konica Minolta, thickness 40 μm) was bonded to both sides of the obtained polarizer by a clamping roller via an aqueous adhesive. The resulting bond was dried at 60° C. for 2 minutes while maintaining the tension of the bonded product at 430 N / m, thereby obtaining a polarizing plate having triacetyl cellulose films as protective films on both sides. It should be noted that the aqueous adhesive was prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318, manufactured by Kuraray) and 1.5 parts of a water-soluble polyamide epoxy resin (Sumirez Resin 650, manufactured by Sumika ChemteX, an aqueous solution with a solid content concentration of 30%) to 100 parts of water.
[0221] [Manufacturing of 1 / 2 wavelength layer]
[0222] The λ / 2 orientation treatment was performed by coating an orientation film coating liquid on a transparent resin substrate and drying it. Then, a coating liquid containing a discotic liquid crystal compound was coated on the orientation surface, and the orientation of the liquid crystal compound was fixed by heating and UV irradiation, thereby preparing a 1 / 2 wavelength layer having a phase difference display layer with a thickness of 2 μm on a transparent resin substrate. The refractive index n11 of the obtained 1 / 2 wavelength layer in the fast axis direction at a wavelength of 589 nm was y is 1.50, and the refractive index in the slow axis direction is n11 xis 1.62, and the refractive index in the thickness direction is n11 z is 1.62. According to the three refractive indices n11 x 、n11 y 、n11 z The calculated three-dimensional average refractive index n11 x,y,z is 1.58, according to the two refractive indices n11 in the plane x 、n11 y The calculated in-plane average refractive index n11 x,y is 1.56.
[0223] [Manufacturing of 1 / 4 wavelength layer]
[0224] The λ / 4 orientation treatment was performed by coating an orientation film coating liquid on a transparent resin substrate and drying it. Then, a coating liquid containing a rod-shaped and polymerizable nematic liquid crystal monomer was coated on the orientation surface and cured while maintaining the refractive index anisotropy, thereby producing a 1 / 4 wavelength layer having a phase difference display layer with a thickness of 1 μm on a transparent resin substrate. The refractive index of the obtained 1 / 4 wavelength layer in the fast axis direction at a wavelength of 589 nm was n12 y is 1.49, and the refractive index in the slow axis direction is n12 x is 1.60, and the refractive index in the thickness direction is n12 z is 1.49. According to the 3 refractive index n12 x 、n12 y 、n12 z The calculated three-dimensional average refractive index n12 x,y,z is 1.53, according to the two refractive indices n12 in the plane x 、n12 y The calculated in-plane average refractive index n12 x,y is 1.55.
[0225] <Example 1>
[0226] The obtained 1 / 4 wavelength phase difference display layer and the 1 / 2 wavelength phase difference display layer were subjected to corona treatment. The adhesive A in Table 1 was applied to the phase difference display layer of the 1 / 4 wavelength layer subjected to corona treatment, and the 1 / 2 wavelength layers were stacked in such a manner that the phase difference display layer sides of the 1 / 2 wavelength layer subjected to corona treatment faced each other and were bonded together using a laminator to obtain a laminate. At this time, the angle between the slow axis of the 1 / 2 wavelength layer and the slow axis of the 1 / 4 wavelength layer was 60°.
[0227] From the 1 / 4 wavelength layer of the laminate, an ultraviolet irradiation device (manufactured by Fusion UV Systems Co., Ltd.) was used to irradiate the laminate at a cumulative light intensity of 400 mJ / cm 2(UV-B) ultraviolet rays were irradiated to cure the adhesive, and a composite retardation plate having a laminated structure of “1 / 4 wavelength layer” / first adhesive layer / “1 / 2 wavelength layer” was obtained. The thickness of the first adhesive layer was 1.5 μm.
[0228] The oriented film and transparent resin substrate of the 1 / 2 wavelength layer of the obtained composite phase difference plate were peeled off, and the polarizing plate and the phase difference display layer of the 1 / 2 wavelength layer were bonded together using an acrylic adhesive. It should be noted that the film thickness of the acrylic adhesive (the film thickness of the second adhesive layer) was 5 μm, and the angle between the transmission axis of the polarizing plate and the fast axis of the 1 / 2 wavelength layer (referred to as "axis angle" in Table 1) was 15°.
[0229] Then, the alignment film and the transparent resin substrate on the 1 / 4 wavelength layer side were peeled off to obtain a polarizing plate composite having a laminated structure of polarizing plate / second adhesive layer / "1 / 2 wavelength layer" / first adhesive layer / "1 / 4 wavelength layer".
[0230] <Example 2>
[0231] A polarizing plate composite was produced in the same manner as in Example 1 except that Adhesive B was used as the adhesive forming the first adhesive layer.
[0232] <Example 3>
[0233] A polarizing plate composite was produced in the same manner as in Example 1 except that Adhesive C was used as the adhesive forming the first adhesive layer.
[0234] <Example 4>
[0235] A polarizing plate composite was produced in the same manner as in Example 1 except that Adhesive D was used as the adhesive forming the first adhesive layer.
[0236] <Comparative Example 1>
[0237] A polarizing plate composite was produced in the same manner as in Example 1 except that Adhesive E was used as the adhesive forming the first adhesive layer.
[0238] <Comparative Example 2>
[0239] A polarizing plate composite was produced in the same manner as in Example 1 except that Adhesive F was used as the adhesive forming the first adhesive.
[0240] <Comparative Example 3>
[0241] A polarizing plate composite was produced in the same manner as in Example 1 except that the polarizing plates were bonded together so that the angle formed by the transmission axis of the polarizing plate and the fast axis of the half wavelength layer (referred to as “axis angle” in Table 1) was 105°.
[0242] [Evaluation method]
[0243] (Interference unevenness evaluation method)
[0244] The polarizing plate composites of Examples and Comparative Examples were bonded to an aluminum reflective plate via an acrylic adhesive (film thickness: 25 μm), visually observed under a trichromatic fluorescent lamp, and evaluated based on the following criteria.
[0245] Table 2 shows the evaluation results.
[0246] A: No interference unevenness was observed
[0247] B: Slightly observed interference unevenness
[0248] C: Uneven interference is observed
[0249] [Table 2]
[0250]
[0251] Description of Reference Numerals
[0252] 10 polarizing plate composite, 11 1 / 2 wavelength layer, 12 1 / 4 wavelength layer, 13 linear polarizing plate, 21 1st adhesive layer, 22 2nd adhesive layer, 30 phase difference plate, 31 substrate layer, 32 orientation layer, 33 phase difference display layer, 40 composite phase difference plate, 111 1st substrate layer, 112 1st orientation layer, 113 1st phase difference display layer, 121 2nd substrate layer, 122 2nd orientation layer, 123 2nd phase difference display layer.
Claims
1. A polarizing plate composite, The invention comprises, in this order, a linear polarizing plate, a half-wave layer, a first adhesive layer formed by curing an active energy ray-curable adhesive, and a quarter-wave layer. The angle between the fast axis of the 1 / 2 wavelength layer and the transmission axis of the linear polarizing plate is 10° or more and 20° or less, An absolute value of a difference between a refractive index of the first adhesive layer at a wavelength of 589 nm and a refractive index of the half wavelength layer in a fast axis direction at a wavelength of 589 nm is less than 0.
05.
2. The polarizing plate composite according to claim 1, wherein: The refractive index of the first adhesive layer at a wavelength of 589 nm is less than 1.
55.
3. The polarizing plate composite according to claim 1 or 2, wherein: The in-plane average refractive index of the quarter wavelength layer at a wavelength of 589 nm is less than 1.58, and the in-plane average refractive index is an average of the refractive index in the fast axis direction and the refractive index in the slow axis direction.
4. The polarizing plate composite according to any one of claims 1 to 3, wherein The absolute value of the difference between the refractive index of the first adhesive layer at a wavelength of 589 nm and the in-plane average refractive index of the quarter wavelength layer at a wavelength of 589 nm is less than 0.05, and the in-plane average refractive index is the average of the refractive index in the fast axis direction and the refractive index in the slow axis direction. 5 . The polarizing plate composite according to claim 1 , which is a circularly polarizing plate.
6. The polarizing plate composite according to any one of claims 1 to 5, wherein The 1 / 2 wavelength layer includes a phase difference display layer as a liquid crystal layer.
7. The polarizing plate composite according to any one of claims 1 to 6, wherein The quarter wavelength layer includes a phase difference display layer as a liquid crystal layer.
8. The polarizing plate composite according to any one of claims 1 to 7, wherein The first adhesive layer has a thickness of 5 μm or less.
9. An image display device, comprising: Image display panel, and The polarizing plate composite according to any one of claims 1 to 8, which is disposed on the viewing side of the image display panel.
10. The image display device according to claim 9, wherein: The polarizing plate complex is arranged in a direction in which the linear polarizing plate is located on the viewing side. 11 . The image display device according to claim 9 , which is an organic electroluminescent display device.
Citation Information
Patent Citations
JP1975083482A
Production of stretched film or sheet
JP1990113920A
polymerizable liquid crystal compound
JP1999513019A
Liquid crystal compound, liquid crystyal composition, polymer, retardation plate, and elliptical polarization plate
JP2005289980A
Polarizing plate and liquid crystal display device
JP2007108732A